Landing kinematics after a sport-specific task in team handball - Bouwmeester, L.; Janssen, I.; Benjaminse, A. (ISBS Proceedings Archive (Michigan), 2020)
Currently, screening for ACL injury risk is mostly conducted in a laboratory setting using a drop vertical jump. There remains a lack of knowledge on lower extremity kinematics and injury risk during sport-specific landing movements. Therefore the purpose of this study was to describe the landing kinematics of elite female handball players after a jump shot in a sport-specific field test. Players` 3D knee and trunk angles were measured using inertial sensors during landing from a jump shot. Average knee flexion at initial contact (IC) was 19.7° ± 5.9 and range of motion (ROM) was 26.2° ± 14.9. Significant between-player differences for all joint angles at IC and ROM were observed. As a variety of landing strategies were utilised, the question arises whether the drop vertical jump test in the lab setting is ecologically valid for identifying ACL injury risk in the field.